Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1093/ajcn/nqy393
|View full text |Cite
|
Sign up to set email alerts
|

Iodine deficiency among Italian children and adolescents assessed through 24-hour urinary iodine excretion

Abstract: Background Iodine is an essential micronutrient for intellectual development in children. Information on iodine intakes based on 24-h urinary iodine excretion (UIE) is scant, because iodine status is only assessed by the measurement of urinary iodine concentration (UIC) in spot urine samples. Objectives The aim of our study was to evaluate the iodine intake of school-age children and adolescents, using UIE measurement in 24-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…They are in keeping with the recently published results of another study carried out by our research group in a sample of the pediatric population in the same period. In this parallel study, involving a sample of 1270 healthy children and adoles-cents recruited in 10 Italian regions, approximately 50% of the female participants had a lower than adequate iodine intake [20]. Approximately, in the same period (2007)(2008)(2009)(2010)(2011)(2012), an OSNAMI survey conducted on 7455 11-14 years school children residing in nine Italian regions showed that most of the regions were still iodine deficient having a median spot UIC less than 100 µg/L [16,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are in keeping with the recently published results of another study carried out by our research group in a sample of the pediatric population in the same period. In this parallel study, involving a sample of 1270 healthy children and adoles-cents recruited in 10 Italian regions, approximately 50% of the female participants had a lower than adequate iodine intake [20]. Approximately, in the same period (2007)(2008)(2009)(2010)(2011)(2012), an OSNAMI survey conducted on 7455 11-14 years school children residing in nine Italian regions showed that most of the regions were still iodine deficient having a median spot UIC less than 100 µg/L [16,21].…”
Section: Discussionmentioning
confidence: 99%
“…Creatinine and iodine measurements were carried out centrally, respectively, at the Departments of Clinical Medicine and Surgery and at the Department of Translational Medical Science, at Federico II University of Naples Medical School. Urinary iodine was analyzed as previously described [20] by an Autoanalyzer 3 system (Bran + Luebbe GmbH, Norderstedt, Germany), using the ceric-arsenious acid reaction and a modified digestion method, with the conventional acid digestion replaced by ultraviolet irradiation. Twenty-four-hour urinary iodine excretion (UIE) was expressed as micrograms per 24 h. Since 92% of the ingested iodine is excreted in urines [7,8], the daily iodine intake (DII) was estimated with the formula: DII (µg/d) = UIE/0.92 Urinary creatinine, measured by the kinetic Jaffé reaction using an ABX Pentra 400 apparatus (HORIBA ABX, Rome, Italy), was used as an indicator to assess the adequacy of the 24 h collection.…”
Section: Iodine Intake Assessmentmentioning
confidence: 99%
“…The estimate of iodine intake and salt consumption was made by measuring iodine and sodium excretion using 24 h urine collections. A detailed description of the study participants' recruitment methods and the procedures used for the collection of demographic and anthropometric data, as well as of the biological samples, has been previously reported [ 11 , 12 ]. Briefly, one thousand two hundred and seventy healthy participants aged 6–17 years, whose parents or legal tutor agreed to let them participate in the study, performed a 24-h urinary collection and underwent a standard physical examination, and an anthropometric evaluation, including measurement of height and weight and calculation of body mass index (BMI) and BMI Z-score, as previously described [ 11 , 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…Between 2011 and 2012, the percentages of iodized salt sold for household use and for the catering system were, respectively, 50% and 23% according to the Italian Ministry of Health [ 10 ]. However, a survey carried out by our group in a national sample of Italian school children and adolescents in 2012 [ 11 , 12 ] showed that a sizable proportion of this young population, especially girls, had a lower than adequate iodine intake despite having a salt intake greater than that recommended by WHO. Thus, the present study aimed to analyse the relationship between salt consumption and iodine intake in the same population and to estimate the actual contribution made by the use of iodized salt to iodine intake.…”
Section: Introductionmentioning
confidence: 99%
“…Most data on iodine intake in Italy are collected in schoolchildren and women of reproductive age, which are the two groups most sensitive to the lack of iodine. Although these data have documented improvements in the last 5-10 years, the target of iodine sufficiency has not been completely achieved [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%